Assessment of Knowledge on Cardiovascular Disease Risk Factors Among Diabetes Mellitus Patients in Tikur Anbessa Specialized Hospital, Ethiopia 2021: A Cross-Sectional Study - Filipos Alemu; Lemlem Beza; Tilahun Jiru; Dereje Endale (Nursing Research and Practice)
Conclusion: This study revealed that almost half of diabetes mellitus patients had suboptimal knowledge about CVD risk factors. Urban residence, higher education level, employment, and information about CVD risk factors are positively associated with good knowledge of CVD risk factors. Health education is needed to improve their knowledge.